EFFECT OF NISTHUSHAYADIKWATHA AND PHALATRIKADI KWATHA IN AMLAPITHA– A RANDOMISED COMPARATIVE CLINICAL STUDY (International Journal of Ayurveda and Pharma Research, 2020)
Amlapitta may be a clinical entity manifesting within the Annavaha Srotas. Kashyapa and Madhava have described this disease thoroughly. Amlapitta has become quite common because of the change within the food and life styles, sophistication and a stressful life. It is characterized by Avipaka, Klama, Tiktodhgara, Amlodhgara, Gaurava, Hritkanthadaha and Aruchi indicating the Vikruthi of Pachakapitta, Kledakakapha and Samanavata. The etiological factors and therefore the symptomatology manifested relate Amlapitta to diseases mentioned under Acid Peptic Disorders. Nistushayadi Kwatha and Phalatrikadi kwatha were selected. The main objectives of the study are to study and compare the effect of Nistushayadi Kwatha and effect of Phalatrikadi kwatha in the management of Amlapitta.A total of 40 patients who fulfilled the inclusion criteria were selected, and randomly assigned into two groups i.e., Group A and Group B, comprising of 20 patients each. Group A and Group B were administered Nistushayadi kwatha and Phalatrikadi Kwatha respectively for 30 days. Both the groups were advised Pathya Ahara. They were followed up after every 10th days. After the intervention the Samanya Lakshana of Amlapitta were observed, recorded and assessed. The overall assessment of both the groups, where group A receives Nistushyadi kwatha and group B Phalatrikadi kwatha shows promising improvement in the subjective parameters. Assessment was done using unpaired ‘t’ test between these two groups, the result was not quite statistically significant which means there is no much difference in the efficacy of these two formulation in the management of Amlapitta. Both the formulations shown nearly same outcome in the improvement of disease parameter. The reduction in the symptoms were started to be noticed by 7th day where the patients had reduction in Hrutkantha Daha, Aruchi, Kanthadaha and Angagourav. These symptoms resolved by 30th day.